GUIDED IMAGERY TECHNIQUES IN REDUCE BREAST CANCER PATIENT PAIN: LITERATURE REVIEW - Sulasri - Sulasri; Kadek Ayu Erika; Rini Rachmawaty (Journal of Nursing Science Update (JNSU), 2018)
Breast cancer is the most common disease in women than men. The most common signs and symptoms in breast cancer are pain. Pain management in cancer patients can be done with pharmacological and non-pharmacological approaches. Non-pharmacological treatment can be one of them is guided imagery techniques. Guided imagery techniques have been widely used in patient care in reducing pain in cancer patients, but there are still very few who discuss pain management in breast cancer patients. This article review was conducted to analyze the effectiveness of guided imagery in reducing pain. Search databases using electronic databases include Proquest, Pubmed, EBSCOhost, Sciensdirect and Google Scholar with keyword strategies: breast cancer, guided imagery, usually care, reduce pain and found 20 articles as references. Review of articles found that guided imagery can reduce pain in cancer patients. Guided imagery can be an alternative choice for actions to reduce pain in breast cancer patients.